(3JaSjQ PGJ GdMdb GdJi PcQgG Kjhf GdEScfOQGfis
(3ChdgG (B:s
(3Ef GdMceGA YedhG ddPi YedhG eKGdkG ddadc djYQahG HgG MSGH JOGhjQ Gdadc hENJdGa Gddjd hGdfgGQ ai CbGdje GdCQV s
(3BNQgG (B:s
(3ajfHZi def CQGO Cf jYed deYQag GdWhd HJbOjQ GdeSjQ Cf jHOC afbOQ Pdc MJi jYde ce ebOGQ GdLRA gfGc ef eSjQ GdCjGe hGdaQGSN hGdCejGd , Ke jYed HYO Pdc adG fNWF Ef TGA Gddg Je GdCHhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B6s
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3505(6)) s
Keywords: (3Gdadcs